RANCANG BANGUN SISTEM INFORMASI ADMINISTRASI AKADEMIK BERBASIS WEB PADA SMA TA’MIRIYAH SURABAYA - Muhammad Ivan Setiawan; Bambang Hariadi; Endra Rahmawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
This research aims to design and build academic administration information system web based at Ta'miriyah senior high school in Surabaya. On this research analysis and design of the system using the method of System Development Life Cycle (SDLC) model waterfall. This methodology includes a number of phases, namely the stage of system analysis, system design and implementation of the system. The data used in this architecture is data grade X period 2015-2016, an active teacher data, and the data subjects that have been designated by the Administration. The results of this final project is design and build academic administration information system web based that can be used by parents to monitor their children activities in relation to the information school administration. For further development may be suggested to make android-based system as well as the added summary and download report Administration information.